Eksistensi Sanggah Kamulan Panganten Di Desa Pakraman Bayung Gede Kecamatan Kintamani Kabupaten Bangli (Perspektif Pendidikan Agama Hindu) - I Nengah Degeng (Cetta: Jurnal Ilmu Pendidikan, 2018)
The existence of Sanggah Kemulan Penganten is very unique and only exists in the Desa Pakraman Bayung Gede. Every citizen who is already in the village, is then asked to make a sacred building in the form of Sanggah Kemulan Panganten. For the people of Bayung Gede, this sacred building is devoted to worshiping God in its aspects as bapanta (father), ibunta (mother) and raganta (self), besides worshiping God in Sanggah Kemulan as in general in Bali. The Existence of Sanggah Kamulan The bride in the Desa Pakraman Bayung Gede is a type of traditional typology morphology. The typology has some unique characteristics, namely (1) a simple form of sanggah and made of dapdap wood (sakti) and woven bamboo. (2) The process of making Sanggah Kamulan Bride in calculating good days (Dauh ayu). Disease, pelinggih built by villagers who got married after three days of the marriage procession ended. (3) The process of worship ritual uses the means of assistance. (4) The community after completing pelanggih Sanggah Kamulan Penganten, then made a bullocker.